PENGARUH MEDIA KARTU BERGAMBAR TERHADAP KEDISIPLINAN ANAK USIA 4-5 TAHUN DI KELOMPOK BERMAIN KUNTUM MEKAR KECAMATAN SENAPELAN PEKANBARU - Deswita, Ratna; Umari, Tri; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine how much influence the display card method to discipline children aged 4-5 years in KB Bud Blooming Pekanbaru. The study consists of two variables: the Influence of Media Picture Cards Against Children Aged 4-5 Years discipline in Playgroup Kuntum Mekar Senapelan District Pekanbaru. The study involved 16 subjects, namely 4-5 years old. Methods of data collection in this study using experimental. Data analysis techniques used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos.The results showed there was a significant positive relationship between the method illustrated cards to discipline children aged 4-5 years in KB Bud Blooming Pekanbar City. Based on the results of test results average difference of discipline children before being treated Picture Cards and having been told by the media treatment Picture Cards. Based on the results of the test results of the child's independence difference after using Media Picture Cards are 48.42% influence on child discipline.Keywords: Picture Cards, Discipline